Penerapan Metode VIKOR (Visekriterijumsko Kompromisno Rangiranje) dalam Pengambilan Keputusan Pemilihan Emulator Android pada Komputer - Renny Pusita Sari; Meilia Susanti (STMIK Budi Darma, 2022)
This research is a research on a decision support system in choosing the best android emulator to use on a computer as a topic of discussion. The Android emulator is a software that supports computers, both laptops and other computer devices, to be able to continue to access Android in computer use by simulating Android to a computer device. In choosing an android emulator, problems often arise to use which emulator is the best and in accordance with the specifications of the computer you have, so for this conditioning, emulator experiments must be carried out one by one in an effort to ensure which emulator is of the highest quality and in simulating android on. Decision Support System can be a good approach in selecting an android emulator, with several criteria in determining the best android emulator, the VIKOR method is used because it has a multi-criteria basic concept. The VIKOR method is an approach in ranking alternatives to get the ideal and best solution with the criteria that have been owned and determined. In testing by managing data, it was found that the genymotion emulator had a final result of 0 and became the best emulator. By applying the VIKOR method, android users or emulator seekers, namely the community of game lovers or gamers, and android lovers will help to determine the ideal android emulator according to the specifications and the best emulator quality.